Caractéristiques sociodémographiques des minorités visibles - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Chaudière-Appalaches

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2024)

Socio-Demographic Characteristics of Visible Minorities in RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Chaudière-Appalaches.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2024)

RTS de Chaudière-Appalaches - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Chaudière-Appalaches’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Chaudière-Appalaches, as well as preliminary recommendations to help improve their labour market outcomes.

Profil d’emploi des Québécois d’expression anglaise de Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2024)
Ce rapport a pour objectif de contribuer aux connaissances et à la compréhension de la situation en matière d’emploi au sein des communautés d’expression anglaise dans la région de Chaudière-Appalaches. Il examine les informations les plus complètes et actuelles sur les conditions démographiques et les états de la population active de ces communautés. Les sujets traités incluent le travail, le taux de chômage, le niveau de revenu et le niveau de scolarité afin d’offrir un portrait plus global de l’emploi et de l’employabilité des Québécois d’expression anglaise, qui sont une minorité linguistique dans la région. En plus d’examiner les données démographiques et la population active d’expression anglaise dans cette région, ce profil analyse les principales caractéristiques du marché du travail et des industries au sein desquelles les personnes d’expression anglaise travaillent. Le profil se termine en identifiant plusieurs des défis et des enjeux en matière d’emploi pour les travailleurs d’expression anglaise dans la Chaudière-Appalaches, et en offrant des recommandations préliminaires afin d’aider à améliorer leur situation sur le marché du travail.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and Lévis - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Beauce-Sartigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Bellechasse - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC La Nouvelle-Beauce - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Les Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Chaudiére-Appalaches and MRC Lotbiniére - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Chaudière-Appalaches - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Impact Report : 2021-2022 - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Employment Profile of English Speakers in Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Chaudière-Appalaches’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Chaudière-Appalaches’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Profil d'emploi des Québécois d'expression anglaise au Chaudière-Appalaches - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise de Chaudière-Appalaches en analysant les informations les plus complètes sur la situation démographique et la situation sur le marché du travail des personnes d’expression anglaise de Chaudière-Appalaches. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement d’expression française. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques: personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil étudie également la structure économique de Chaudière-Appalaches, ainsi que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs, dans le but de dresser un portrait d’emploi et d’employabilité plus global.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

VEQ Newsletter December 2021 - Voice of English-speaking Quebec (VEQ) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

VEQ Newsletter November 2021 - Voice of English-speaking Quebec (VEQ) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de Chaudière-Appalaches - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Annual Report : 2020-2021 - Megantic English-speaking Community Development Corporation (MCDC) (2021)

VEQ Newsletter Spring 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter Summer 2021 - Voice of English-speaking Quebec (VEQ) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

39th Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Partners for Better Care - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Annual Report : 2019-2020 - Megantic English-speaking Community Development Corporation (MCDC) (2020)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Annual Report : 2018-2019 - Megantic English-speaking Community Development Corporation (MCDC) (2019)

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Beauce-Sartigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Bellechasse - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Les Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Lévis - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches (1210) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS Alphonse-Desjardins (1211) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de Beauce (1213) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de la région de Thetford (1212) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

2015 CHSSN-CROP Survey on Community Vitality : Findings on English-speaking Community Vitality Across Key Sectors - Pocock, Joanne (Community Health and Social Services Network, 2016)
This 2015-2016 Baseline Data Report relays key findings of the 2015 CHSSN/CROP Survey on Community Vitality as they unfold across key sectors. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income and level of bilingualism. This report from the 2015 survey is intended as a companion to the 2015-2016 Baseline Data Report entitled English Language Access to Health and Social Services in Québec, which includes a summary of results from Focus Group sessions conducted in several regions around the province.

Children 0 to 5 and their Parents : RTS de Chaudière-Appalaches - Community Health and Social Services Network (CHSSN) (2016)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Community Consultation 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Partner Survey 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Beauce Sartigan (12031) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Chaudiere (12022) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Desjardins (12021) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Beauce (1203) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Region de Thetford (1204) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Grand Littoral (1202) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Update - Leading English Education and Resource Network (LEARN) (2012)

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Rapport Annuel 2009-2010 - Leading English Education and Resource Network (LEARN) (2010)
Dans une province aussi vaste que le Québec, où les écoles et les commissions scolaires sont dispersées sur une immense étendue géographique, la notion de rassembler les gens pour en faire une COMMUNAUTÉ de collaboration semble un obstacle gigantesque, sinon insurmontable. Dans la réalité, les gens partagent des intérêts similaires et des objectifs communs et cette notion d’impossibilité physique s’estompe rapidement. Cette évolution est particulièrement vraie quand l’objectif ultime est la réussite scolaire de nos enfants au niveau des écoles élémentaires et secondaires. LEARN a pour objectif de servir de catalyseur et de facilitateur pour la création de communautés de collaboration réunissant les éducateurs, les parents et les élèves à l’échelle de la province. L’objectif de notre organisation est de déployer tous les efforts possibles pour réunir les forces positives du milieu éducatif anglophone afi n de contribuer au partage des connaissances et des expériences disponibles au sein de notre communauté.

Listening to Our Young People : The VEQ Youth Report 2005 - Pitre, Edgard; Tomlinson, Patrick; Twardawa, Christopher (Voice of English-speaking Quebec (VEQ), 2005)
The following represents the findings of a youth study conducted by the Voice of English-speaking Québec (VEQ) in 2004 - Listening to Our Young People. The purpose of the study was to collect and correlate survey responses completed by Secondary IV and V, adult learning centre, and CEGEP 1, 2 and 3 Anglophones in the Greater Quebec City and Chaudières-Appalaches regions. The survey questions varied in scope but the general focus was concerned with the various aspects of daily life in and around Quebec City. By analyzing survey responses, VEQ hoped to arrive at a better understanding of the perceptions, positive and otherwise, young Anglophones have regarding their community.

Citadel Foundation - Donovan, Patrick

Together We Can Help Create an Ideal Learning Environment for All - Leading English Education and Resource Network (LEARN)

In Conversation : A Conversation Club for Health Professionnals of the CISSS Chaudière-Appalaches (Thetford Mines sector) - Megantic English-speaking Community Development Corporation (MCDC)

The Many Faces of Elder Abuse - Voice of English-speaking Quebec (VEQ)
Voice of English-speaking Québec is proud to support English-speaking seniors in the greater Quebec City region. This booklet was produced to help seniors in our community stay independent, safe and to help prevent abuse and discrimination targeting them. This project is funded in part by Service Canada under the New Horizons for Seniors Program.